(untitled) (Bioresearch Communications, 2022)
Skin toning creams and turmeric powders are widely used among Bangladeshi fashion and beauty concerned women and young girls in general. However, it has been reported that excessive use of skin toning cream and turmeric powder can cause various dermatological problems, including skin cancer. These creams and turmeric powder contain a wide variety of active ingredients, including Hydroquinone (HQ), Mercury (Hg), and Lead (Pb), that are toxic, and hazardous to health, especially after prolonged application. As a result, in the current study, we tried to assess HQ and Hg level in commonly used skin toning creams and Pb in turmeric powder in the context of Bangladeshi women collected from the local markets in Dhaka city. HQ, Hg, and Pb levels were analyzed for 40 different Bangladeshi skin toning cream products and 40 different turmeric powder samples. The HQ level was determined by the high-performance liquid chromatography (HPLC) method, the Hg level was determined by Cold Vapor Atomic Absorption Spectrophotometry (CV-AAS) using an automatic mercury analyzer, and Pb was measured by the flame atomic absorption spectrometry method. Among the 40 samples, 23 samples (57.5%) did not contain HQ, whereas 17 samples (42.5%) contained a high level of HQ compared to the standard limit. In the case of Hg analysis, we found that 28 (70%) out of 40 samples complied with the standard level of Hg, whereas 12 samples (30%) contained a higher level of Hg compared to the standard limit. Among the 40 samples of turmeric powder, 20 samples (50%) complied with the standard level of Pb, whereas 20 samples (50%) contained a high level of Pb compared to the standard limit. After three and six months of storage, we had similar results in all the samples for the three cases. After combining HQ and Hg data sets, we found that 14 (35%) out of the 40 samples had HQ and Hg levels within the standard limit, and 3 samples (7.5%) had higher quantities of both HQ and Hg levels and did not comply with the standard limit. 14 samples (35%) in the data set had higher HQ levels but complied only with the standard Hg level, whereas 9 samples (22.5%) had higher Hg levels and thus complied only with the standard HQ level. So, in 65% of the samples, we found the presence of excess level of either both HQ and Hg at the same time or any one of the measured chemical parameters. The use of these creams and turmeric powders, which did not comply with the standard limit, may pose a serious health risk to consumers. So, consumers should be aware of the risks associated with using these creams and turmeric powders, and policymakers should take appropriate measures to prevent the manufacturing and marketing of skin toning creams containing high levels of HQ and Hg and turmeric powder with high levels of Pb. Bioresearch Commu. 8(2): 1132-1142, 2022 (July)